Manajemen Operasional Perusahaan Syariah: Studi Kasus Laznas Lembaga Manajemen Infaq Bangkalan - Suffahurrohman, M Nur; Qadariyah, Lailatul (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The Bangkalan Infaq Management Institute is one of the institutions that has managed to collect ZIS funds and distribute them to mustahiq and programs. This can happen because the operational management implemented by the institution is running well so that the distribution of funds and the implementation of programs are obtained optimally. This research uses qualitative methods and case study methods. Data was collected through in-depth interviews with management and related staff as well as through analysis of documents and 2 financial reports of the Bangkalan Infaq Management Institute. The results of this study indicate that: 1) Planning in operational management implemented by LMI Bangkalan is very good, one of which is: (a) long-term strategic program plans; (b) Design goals and objectives; (c) Building a broadcast fund-based collection scenario. 2) In implementing the management of fundraising by the Bangkalan Infaq Management Institute (LMI), two methods are used, namely the method of direct fundraising through outreach, publishing magazines, and offering programs to partners in collaboration with institutions. While the indirect fundraising method is carried out using various social media and the use of social media. 3) The Bangkalan Infaq Management Institute (LMI) controls 3 things: (a) Development program; (b) fund development; (c) Coordinating the constraints faced both internally and externally to the institution.